1995
DOI: 10.1111/j.1600-0765.1995.tb01289.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of periodontal bacteria and disease status on Vβ expression in T cells

Abstract: Some bacterial antigens such as S. aureus enterotoxins can selectively stimulate T cells that express specific V beta genes of the T cell antigen receptor (TCR). The purpose of this study was to investigate whether or not periodontal bacteria could similarly alter the expression of V beta families within the TCR complex. Peripheral blood mononuclear cells (PBMNCs) were isolated from 12 patients with early onset periodontitis and 11 periodontally-healthy controls. PBMNCs were incubated in media alone, or co-cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 9 publications
4
25
0
1
Order By: Relevance
“…We found that baseline expression of V,B2 and Vf8 was significantly higher in the peripheral blood of individuals with disease when compared with healthy individuals (Mathur et al, 1995). Interestingly, when the peripheral blood mononuclear cells (PBMNCs) of periodontally healthy or diseased individuals were co-cultured for 48 hours with heat-inactivated Prevotella intermedia, the majority of healthy and diseased individuals (regardless of disease status) demonstrated increased expression of VWP2+, V35+, or V136+ cells (Mathur et al, 1995).…”
Section: A) Proliferative Responses Of Peripheral Blood (Pb) T-lymphomentioning
confidence: 93%
See 1 more Smart Citation
“…We found that baseline expression of V,B2 and Vf8 was significantly higher in the peripheral blood of individuals with disease when compared with healthy individuals (Mathur et al, 1995). Interestingly, when the peripheral blood mononuclear cells (PBMNCs) of periodontally healthy or diseased individuals were co-cultured for 48 hours with heat-inactivated Prevotella intermedia, the majority of healthy and diseased individuals (regardless of disease status) demonstrated increased expression of VWP2+, V35+, or V136+ cells (Mathur et al, 1995).…”
Section: A) Proliferative Responses Of Peripheral Blood (Pb) T-lymphomentioning
confidence: 93%
“…This skewing of receptor expression might be explained in at least two ways. First, bacteria present in the periodontal pockets or sulci may contain antigens which selectively stimulate cells which express a particular VP receptor (Mathur et al, 1995). Second, homing of cells to diseased tissues may be mediated in part by VP3 receptor expression.…”
Section: A) Proliferative Responses Of Peripheral Blood (Pb) T-lymphomentioning
confidence: 99%
“…In this regard, there are reports suggesting that lipopolysaccharides (LPS) (11,30,31) and other surface components (12,21,29) isolated from P. intermedia are capable of inducing inflammatory lymphokines, which may contribute to the pathological inflammatory mechanisms that are operative in periodontal disease. Recently, there has been evidence to suggest that some periodontopathic organisms may be involved in the activation of T cells expressing specific variable regions on the ␤ chain (V␤) of T-cell receptors (TCRs) (8,19,20,37). One study showed that up to 50% of all gingival T cells express unique subsets of V␤ TCRs in most periodontitis patients but not in healthy subjects (37).…”
mentioning
confidence: 99%
“…For 2-week cultures, fresh medium supplemented with 1 g of ISTF/ml and 2 U of IL-2/ml was added every 3 days. tion by periodontopathic bacteria, which induces large-scale T-cell activation, cytokine production, and polyclonal B-cell activation (1,16,17,32). In this study, we have determined whether ISTF had the ability to activate naive T cells in a manner consistent with their activation by a known superantigen, SEB.…”
Section: Fig 7 Representative Histogram Of B220mentioning
confidence: 99%
“…Lipopolysaccharide (LPS) suppressed antigen-and mitogen-induced human T-cell proliferation by inducing the release of prostaglandin E2 from activated macrophages (5). As all these factors contributed to the suppression of lymphocyte activation, it has been suggested that products of A. actinomycetemcomitans might possess a lymphocyte-activating substance like a superantigen (1,16,17,32). During studies in our laboratory focusing on an understanding of the immunomodulatory activity of the products from A. actinomycetemcomitans, we became intrigued by an indication that immunosuppressing and immunostimulating activities were present simultaneously in the bacterial preparations.…”
mentioning
confidence: 99%